Interferon γ improves the vaccination potential of oncolytic parvovirus H-1PV for the treatment of peritoneal carcinomatosis in pancreatic cancer - Grekova, Svitlana; Aprahamian, Marc; Daeffler, Laurent; Leuchs, Barbara; Angelova, Assia; Giese, Thomas; Galabov, Angel; Heller, Anette; Giese, Nathalia; Rommelaere, Jean; Raykov, Zahari Zahariev (Cancer biology & therapy, 2011)
Oncolytic viruses with their capacity to specifically replicate in and kill tumor cells emerged as a novel class of cancer therapeutics. Rat oncolytic parvovirus (H-1PV) was used to treat different types of cancer in preclinical settings and was lately successfully combined with standard gemcitabine chemotherapy in treating pancreatic ductal adenocarcinoma (PDAC) in rats. Our previous work showed that the immune system and particularly the release of interferon-gamma (IFNγ) seem to mediate the anticancer effect of H-1PV in that model. Therefore, we reasoned that the therapeutic properties of H-1PV can be boosted with IFNγ for the treatment of late incurable stages of PDAC like peritoneal carcinomatosis. Rats bearing established orthotopic pancreatic carcinomas with peritoneal metastases were treated with a single intratumoral (i.t.) or intraperitoneal (i.p.) injection of 5x108 plaque forming units of H-1PV with or without concomitant IFNγ application. Intratumoral injection proved to be more effective than the intraperitoneal route in controlling the growth of both the primary pancreatic tumors and peritoneal carcinomatosis, accompanied by migration of virus from primary to metastatic deposits. Concomitant i.p. treatment of H-1PV with recIFNγ resulted in improved therapeutic effect yielding an extended animal survival, compared with i.p. treatment with H-1PV alone. IFNγ application enhanced the H-1PV-induced peritoneal macrophage and splenocyte responses against tumor cells while causing a significant reduction in the titers of H1-PV-neutralising antibodies in ascitic fluid. Thus, IFNγ co-application together with H-1PV might be considered as a novel therapeutic option to improve the survival of PDAC patients with peritoneal carcinomatosis.
Gesehen am 11.07.2022